China's Global Security Initiative: Its Objectives and Implications for Southeast Asia - Yuliantoro, Nur Rachmat (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
China has introduced several initiatives aimed at further strengthening its influence both regionally and globally. As a complement to the Belt and Road Initiative, the Chinese government also launched the trio of Global Development Initiative, Global Security Initiative, and Global Civilization Initiative. The Global Security Initiative (GSI) has received widespread attention regarding its meaning, strategy, objectives, and implications for China’s role in international security and peace. By looking at this issue from the current dynamics of global security, this study invites us to understand what the GSI is and the goals that China wants to achieve with it, especially in Southeast Asia. The implications of the GSI for the region’s economic development and stability are also highlighted. China intends the GSI to act as a “broker” for achieving world peace, with strategic consequences for the stability of the Southeast Asian region.Keywords: China; Global Security Initiative; Southeast Asia; regional stability; economic development.Dewasa ini Cina telah memperkenalkan beberapa inisiatif yang ditujukan untuk semakin memperkuat pengaruhnya baik secara regional maupun global. Sebagai pelengkap dari Belt and Road Initiative, pemerintah Cina juga meluncurkan trio Global Development Initiative, Global Security Initiative, dan Global Civilization Initiative. Global Security Initiative (GSI) mendapatkan perhatian yang luas terkait dengan makna, strategi, tujuan, dan implikasinya bagi peran Cina dalam keamanan dan perdamaian internasional. Dengan melihat isu ini dari dinamika keamanan global yang berlaku, studi ini mengajak kita untuk memahami apa sesungguhnya GSI serta tujuan yang hendak Cina capai dengannya, khususnya di Asia Tenggara. Implikasi dari GSI terhadap pembangunan ekonomi dan kestabilan kawasan ini juga disorot oleh studi ini. GSI dimaksudkan oleh Cina untuk berperan sebagai “perantara” bagi upaya mencapai perdamaian dunia, dengan konsekuensi-konsekuensi strategis bagi kestabilan kawasan Asia Tenggara.Kata-kata Kunci: Cina; Global Security Initiative; Asia Tenggara; stabilitas kawasan; pembangunan ekonomi.